Securing compliance: Some lessons for EU strategy on occupational health and safety - David Walters; Richard Johnstone; Elizabeth Bluff; Hans Jørgen Limborg; Ulrik Gensby (European Trade Union Institute (ETUI), 2021)
This paper discusses findings from a review of recent literature on support for securing compliance and better practice in occupational safety and health (OSH) in the changing world of work in advanced market economies. It explores innovative responses of regulators and private actors to the challenges created by these changes, as well as considering their impact on further forms of support for good practice, such as provided by prevention services and OSH professionals. Although the review is based on a wide-ranging search of the literature in English, its discussion is focused on implications for prevention policies in the European Union. In particular, it considers the extent to which the literature suggests that the current strategic framework for supporting compliance - via EU policies over the past two decades, with a new Strategic Framework anticipated in 2021 - can be said to address these challenges effectively. Not surprisingly, it finds that the literature reveals some gaps between the policy rhetoric and the practice at both EU and Member State levels.
Keywords: 330; working world; occupational health and safety; compliance management; EU law; EU countries; Arbeitswelt; Arbeitsschutz; Compliance-Management; EU-Recht; EU-Staaten